2021
DOI: 10.1590/1806-9282.20201015
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metalloproteinases 2 and 9 and plasma zinc concentrations in women with fibroadenoma

Abstract: OBJECTIVE: This study aims to investigate the association between the immunohistochemical expression of matrix metalloproteinase-2 and matrix metalloproteinase-9 and plasma zinc in women with fibroadenoma. METHODS:This cross-sectional study included 37 premenopausal women with fibroadenoma. Waist circumference and body mass index of the participants were measured. Plasma zinc concentrations were determined using atomic flame absorption spectrophotometry. Fragments of breast tissue were fixed and incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…In our study, Cu, Fe, and Mn showed no relationship with MMPs, their TIMPs and CT, whereas Zn was inversely related with the MMPs of the study, but not with their TIMPs. Similarly to our results, situations of hypozincemia have been reported to be directly related to positive expression of MMPs 2 and 9, but in non-tumorous samples [30]. Moreover, although TIMPs are usually designed to interact with Zn ions in the catalytic domain, thus interfering with enzymatic activity [31], Zn did not correlate with TIMPs in our samples.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, Cu, Fe, and Mn showed no relationship with MMPs, their TIMPs and CT, whereas Zn was inversely related with the MMPs of the study, but not with their TIMPs. Similarly to our results, situations of hypozincemia have been reported to be directly related to positive expression of MMPs 2 and 9, but in non-tumorous samples [30]. Moreover, although TIMPs are usually designed to interact with Zn ions in the catalytic domain, thus interfering with enzymatic activity [31], Zn did not correlate with TIMPs in our samples.…”
Section: Discussionsupporting
confidence: 87%